2011
DOI: 10.1523/jneurosci.3354-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Instrumental Contingency Learning: Differential Effects of Action–Reward Conjunction and Disjunction

Abstract: Contingency theories of goal-directed action propose that experienced disjunctions between an action and its specific consequences, as well as conjunctions between these events, contribute to encoding the action-outcome association. Although considerable behavioral research in rats and humans has provided evidence for this proposal, relatively little is known about the neural processes that contribute to the two components of the contingency calculation. Specifically, while recent findings suggest that the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
124
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(133 citation statements)
references
References 31 publications
9
124
0
Order By: Relevance
“…In particular, we found that activity in the OFC tracked the chosen action contingency, which is equivalent to the expected reward value in this task. A number of studies have found expected reward signals in this region1427282930313233, as well as the medial prefrontal cortex3235 and amygdala36. Some studies have also found that the reward signal in the OFC precedes the dlPFC response37, which implies that reward value information is relayed from the OFC to the dlPFC.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we found that activity in the OFC tracked the chosen action contingency, which is equivalent to the expected reward value in this task. A number of studies have found expected reward signals in this region1427282930313233, as well as the medial prefrontal cortex3235 and amygdala36. Some studies have also found that the reward signal in the OFC precedes the dlPFC response37, which implies that reward value information is relayed from the OFC to the dlPFC.…”
Section: Discussionmentioning
confidence: 99%
“…One system, called the “act/outcome” system, is sensitive to the contingency between response and reinforcer. Contingency is “the difference between the probability of obtaining a target reward (r) given that a specific action (a) is performed and the probability of gaining the reward in the absence of the action” (Liljeholm, Tricomi, O'Doherty, & Balleine, 2011, p. 2474). The act/outcome system leads to “flexible” learning, and it is sensitive to contingency changes in the reward.…”
Section: The Neural Circuitry Of Learned Helplessnessmentioning
confidence: 99%
“…Whereas parietal and temporal association cortices surround visual, auditory, and somatosensory areas, the ventromedial/orbitofrontal cortex and the anterior insula are adjacent to primary olfactory and gustatory areas (Rolls, 2000). Neurophysiological studies in laboratory animals and functional imaging in humans show that associative memory to rewarding or aversive experiences are stored in these areas (Balleine, Leung, & Ostlund, 2011;Gottfried & Zelano, 2011;Howard, Gottfried, Tobler, & Kahnt, 2015;Liljeholm, Tricomi, O'Doherty, & Balleine, 2011;Noonan, Kolling, Walton, & Rushworth, 2012;Parkes, Bradfield, & Balleine, 2015;Rudebeck, Saunders, Prescott, Chau, & Murray, 2013;Schoenbaum, Roesch, Stalnaker, & Takahashi, 2009).…”
Section: Implicit Emotion Regulationmentioning
confidence: 99%